NGOs' initiatives and grassroots approach for accessing to health care services for the slum people in Dhaka - Bhuiyan, Mohammad Ismail; Haque, Md. Aminul (Frontiers in Health Services, 2024)
ObjectiveThis study holds significant importance as it aims to delve into the impactful NGOs’ initiatives and grassroots approaches instrumental in providing healthcare services to Dhaka's underserved slum people. It focuses on understanding how these factors influence the use and access to health services, which is a crucial aspect for researchers, policymakers, and healthcare professionals.Study designThis study was meticulously designed, utilizing a comprehensive cross-sectional mixed-methods design. By incorporating qualitative and quantitative data collection methods, we ensured a thorough understanding of NGOs’ initiatives and grassroots approaches to providing healthcare services to slum dwellers in Dhaka, thereby instilling confidence in the validity of our research for the audience.MethodsA face-to-face interview was used to survey the participants (n = 722) using semi-structured questionnaires, following a systematic sampling technique. Four focus group discussions (FGDs) were also conducted with the slum people. Binary logistic regression was performed to know NGOs’ initiatives, roles, and grassroots approach as predictors or independent variables and healthcare services as an outcome or dependent variable. The quantitative data were analyzed using SPSS version 23.0. At the same time, thematic analysis was conducted following Philip Adu's Qualitative data analysis process and Braun and Clarke's six steps of the thematic analysis system, integrating the 11 subthemes with the quantitative findings to highlight the interpretative findings of the qualitative data.FindingsMajor findings revealed that NGOs’ initiative roles and grassroots approach had a significant impact on slum dwellers’ use and access to healthcare services. The initiatives included affordable health services (OR = 22.86, 95% CI = 3.87, 35.00, P = 0.01), special health services (OR = 5.63, 95% CI = 3.36, 9.42, P = 0.00), engagement of responsible community leaders (OR = 1.72, 95% CI = 1.14, 2.59, P = 0.01), distribution of health and medicine items (OR = 1.92, 95% 2 CI = 1.40, 2.63, P = 0.01), provision of updated information to slum dwellers (OR = 1.37, 95% CI = .99, 1.90, P = 0.05), telehealth and telemedicine (OR = 1.82, 95% CI = 1.55, 2.13, P = 0.01), BCC strategy (OR = 1.26, 95% CI = 1.00, 1.57, P = 0.05), and doorstep services as NGOs’ grassroots approach (OR = 1.84, 95% CI = 1.00, 3.38, P = 0.05). Qualitative findings supported the quantitative findings through 2 main themes and 11 sub-themes, which were integrated with quantitative findings to highlight the interpretative findings of qualitative data.ConclusionsHealth services and other facilities for urban slum people through NGOs’ initiatives and grassroots approaches are highly affordable and practical, special health services with the involvement of special exceptional health professionals, community supportive services, BCC strategies, and doorstep health services may trigger the use and access to health services for slum dwellers. Results suggest and recommend capitalizing and investing in such initiatives and grassroots approaches from the government, policymakers, and donors with NGOs to find accessible, affordable health services for the unprivileged slum people.